Integrasi Asas Andragogi Dengan Pembelajaran Muhadastah: Studi Kasus LPBA MASA Surabaya - Laili Mas Ulliyah Hasan; Muhammad Tareh Aziz; Firdausi Nurharini (Program Studi Pendidikan Bahasa Arab Universitas Nahdlatul Ulama Purwokerto, 2024)
This research aims to explore and analyze Muhadastah's learning competencies by applying the principles of Andragogy at the Arabic Language Education Institute (LPBA) at the Great Mosque of Sunan Ampel (MASA) Surabaya. The research methodology uses qualitative methods with participants consisting of students and teachers who are involved in Muhadastah learning at LPBA. Participants were selected purposively to ensure appropriate representation of varying levels of Arabic speaking skills. Data was collected through classroom observations, interviews with teachers, and student questionnaires. Class observations were carried out to observe Muhadastah's learning practices using the principles of Andragogy, while interviews with teachers aimed to gain a deeper understanding of the application of Andragogy principles in Muhadastah's learning. In addition, student questionnaires were used to evaluate their perceptions of Muhadastah learning with this approach. The qualitative data collected will be analyzed using a thematic analysis approach, with data organized, coded, and categorized based on themes that emerge from classroom observations, interviews, and questionnaire responses. The research findings highlight the application of Andragogy principles in Muhadastah learning, the challenges in combining these two concepts, as well as the potential and benefits of integration to improve the quality of Arabic language learning. The recommendations that can be made are teacher training, increasing access to resources, and developing a curriculum that is more oriented to student learning needs.